Murine GRXCR1 Has a Different Function Than GRXCR2 in the Morphogenesis of Stereocilia - Liu, Chang; Zhao, Bo (Frontiers in Cellular Neuroscience, 2021)
Mutations in human Glutaredoxin domain-containing cysteine-rich protein 1 (GRXCR1) and its paralog GRXCR2 have been linked to hearing loss in humans. Although both GRXCR1 and GRXCR2 are required for the morphogenesis of stereocilia in cochlear hair cells, a fundamental question that remains unclear is whether GRXCR1 and GRXCR2 have similar functions in hair cells. Previously, we found that GRXCR2 is critical for the stereocilia morphogenesis by regulating taperin localization at the base of stereocilia. Reducing taperin expression level rescues the morphological defects of stereocilia and hearing loss in Grxcr2-deficient mice. So far, functions of GRXCR1 in mammalian hair cells are still unclear. Grxcr1-deficient hair cells have very thin stereocilia with less F-actin content inside, which is different from Grxcr2-deficient hair cells. In contrast to GRXCR2, which is concentrated at the base of stereocilia, GRXCR1 is diffusely distributed throughout the stereocilia. Notably, GRXCR1 interacts with GRXCR2. In Grxcr1-deficient hair cells, the expression level of GRXCR2 and taperin is reduced. Remarkably, different from that in Grxcr2-deficient mice, reducing taperin expression level does not rescue the morphological defects of stereocilia or hearing loss in Grxcr1-deficient mice. Thus, our findings suggest that GRXCR1 has different functions than GRXCR2 during the morphogenesis of stereocilia.